Parental functioning and social support in families of children with autism spectrum disorders - Felizardo, Sara (2017)
Introduction: Research on the functions of social support in families of children with disabilities in the context of inclusive settings, emphasizes that this concept influence various dimensions of parental and family functioning. Objectives: TThis study aims to analyze the influence of the perception of social support in the parental functioning and development trajectories of families in the context of adaptation to disability and incapacity. Methods: It is a qualitative and comprehensive study of the phenomena. We formed a convenience sample of 10 caregivers of children with ASD. Data collection instrument was a semi-structured interview that covers socio-demographic aspects and other information related to the past, present and future of parental and family development. Results: The analysis of parents discourses suggests a high parental involvement in educational and therapeutic processes, good levels of formal and informal social support, the use of coping strategies focused on solving the problems and positive perceptions on children and on parenting changes; despite these results, speeches indicate a high parental stress resulting from requirements and barriers in the management of daily life. Caregivers are linked to support institutions and reveal close relationships with other parents. Conclusions: The perception of social support emerges as a relevant construct, which must be considered in the context of intervention with families of children with autism. In this sequence, it is proposed areas, measures and actions in the field of family intervention.